A study on the factors that influence the employee retention at Rawang Specialist Hospital Sdn Bhd / Khairunnadia Khairul Azmi and Nur Adriana Farzana Mohamed Ibrahim - Khairul Azmi, Khairunnadia; Mohamed Ibrahim, Nur Adriana Farzana (Faculty of Business and Management, 2016)
Purpose of this study is to identify the factors that influence employee retention among the staff in Rawang specialist Hospital. The researcher have chosen Rawang Specialist Hospital to represent this study. Researchers have listed two variables which are training and development, compensation and organizational culture as independent variables and employee retention as dependent variable. Researchers have distributed 165 sets of questionnaire to the respondents in Rawang Specialist hospital. This study discussed the factors that influence the employee retention in rawang Specialist Hospital. The findings and analysis were made based on Statistical Package for Social science (SPSS) version 21.0 to analyze the data. The findings of this study proves that training and development, compensation and organizational culture positively affect the employee retention to all staff in Rawang Specialist Hospital.